Fotobiomodulação no tratamento de espasticidade em crianças com diagnóstico de paralisia cerebral: estudo cego, controlado, randomizado - Zöll, Ariane Cristina (2025)
Cerebral palsy (CP) is a non-progressive, permanent syndrome that occurs in childhood and in which approximately 80% of patients develop spasticity. When left untreated, spasticity can cause pain, anatomical and structural changes in bones, joints, muscles, tendons and nerve synapses, with a negative impact on the quality of life, social participation and functionality of this individual. Photobiomodulation (PBM) has biological effects of tissue regeneration, muscle relaxation, vasodilation, reduction of the inflammatory process and relief of pain symptoms already described in the literature; in addition to being feasible, practical, safe, painless and non-invasive. Objective: to evaluate the effect of PBM on local spasticity of the right gastrocnemius muscle of children with spastic CP. This is a blinded, randomized, controlled clinical study. Method: 12 children aged 2 to 18 years, diagnosed with spastic cerebral palsy of the lower limbs of any etiology for at least 3 months, selected at the Physiotherapy Service of the Nove de Julho University were randomized into two groups: PBM Group (n = 7) with application of low-intensity LED therapy in the medial and lateral right gastrocnemius muscles (100mW of power, 850nm, 1.5 J per point, applied in 02 points per muscle, by contact, for 15 seconds) once a week, totaling 08 therapeutic days; or Placebo Group (n = 5) (same parameters and method of application, but with the equipment turned off). Both groups also received the standard treatment for spasticity carried out by the hospital's rehabilitation health team. The evaluation of the effect of therapy for the primary outcome was measured by the modified Ashworth Scale (MAS), the Pediatric Disability Assessment Inventory (PEDI), the Gross Motor Function Classification System (GMFCS) scale and the passive range of motion of the ankle analyzed at the end of each therapeutic session of PBM and in the pre and post therapeutic periods of 08 weeks. Result: a preliminary pilot analysis of the included participants (all GMFCS IV or V) showed no statistical difference between the groups for any of the evaluated outcomes. The initial MAS means for the PBM group were 2.14 ± 0.89 and 2.2 ± 0.44 for the Placebo group, and the final MAS was 0.86 ± 0.37 and 1.6 ± 0.54 for the PBM and placebo groups, respectively. There was a significant improvement in MAS between the moments. The participants 11 undergoing PBM did not present worsening of spasticity and there were no adverse events or side effects to PBM. The effect size of PBM for improving spasticity, compared to placebo PBM associated with exercise in these participants identified with n 2 of the ANOVA test, was 0.171. Discussion: New studies should prioritize PBM in a population with smaller GMFCS, application in sites with minimal detectable functional activity and especially in populations that have contraindications or that do not have the opportunity to undergo integrated rehabilitation treatment, so that the therapy can be evaluated in a more specific target population and with more promising effects. Conclusion: This PBM protocol showed positive results in the treatment of triceps surae spasticity in children with Cerebral Palsy in a safe manner. In this study, no short-term adverse events were observed, and the therapeutic period was easy to perform and with good participant adherence.